Electronically Tunable Universal Filter and Quadrature Oscillator Using Low-Voltage Differential Difference Transconductance Amplifiers - Montree Kumngern; Pichai Suksaibul; Fabian Khateb; Tomasz Kulej (My University, 2022)
This paper presents a new electronically tunable universal filter and quadrature oscillator for low frequency biomedical and biosensor applications employing low-voltage differential difference transconductance amplifier (DDTA). The DDTA CMOS structure uses 0.5 V of supply voltage and consumes 277 nW of power. Unlike the previous universal filters, the proposed filter provides many transfer functions of the standard five transfer functions such as low-pass, high-pass, band-pass, band-stop and all-pass with both unity and controlled voltage gains as well as both inverting and non-inverting transfer functions. The natural frequency and the voltage gain of the five standard transfer functions can be controlled electronically. For the band-pass filter, the third intermodulation distortion (IMD3) was 0.37% for 20 mVpp input signal while the output integrated noise was 61.37 $\mu \text{V}$ . The dynamic range (DR) was 53.27 dB for 1% IMD3. The quadrature oscillator has electronically and orthogonal control of the condition and frequency of oscillation. The proposed circuit and its applications were designed and verified via Cadence simulator tool using 0.13 $\mu \text{m}$ UMC CMOS technology. Further, the circuit was evaluated by PSPICE simulation and experiment test using commercial OTA LM13700.
Keywords: Transconductance; Operational transconductance amplifier; Digital biquad filter; Analog and Mixed-Signal Circuit Design